Variabilité de certains paramètres climatiques et impacts sur la durée des périodes humides de développement végétal dans une station au centre et une autre au nord du Burkina Faso - Dasmané Bambara; Jacques Sawadogo; Oumar Kaboré; Ablassé Bilgo (VertigO)
This work is based on weather data from Ouagadougou and Ouahigouya to examine the changes that have affected rainfall, relative humidity (RH) and potential evapotranspiration (FTE) and the impact of these changes on the duration of favorable periods for rainfed crops growth from 1956 to 2015. Pettitt's test and Hubert's segmentation procedure revealed several breaks of homogeneity localized in : (i) 1981 (Ouagadougou), 1973 and 1995 (Ouahigouya) for rainfall, (ii) 1984 (Ouagadougou) for HR, (iii) 1985 and 1994 (Ouagadougou), 1978 and 1992 (Ouahigouya) for ETP. This climatic dynamic goes with a shortening of the wet season duration of -25 % in Ouagadougou and -3 % in Ouahigouya. This shortening is mainly due to the decrease in the duration of the wet periods, which fell by -37 % in Ouagadougou and -12 % in Ouahigouya. Similarly, the duration of the active vegetation period decreased from 102 days before break to 48 days after break (-59 % decrease) in Ouagadougou and from 67 days before break to 21 days after break (-38 % decrease) in Ouahigouya. The diagnosis of climate variability and its impact on the duration of rainfed crops growth periods across the country will better characterize agro-climatic dynamics in order to guide the development of appropriate adaptation strategies.